The Making of Evaluation Instrument Based on HOTS with Wondershare Quiz Creator on Ion Balance and Buffer Solution pH - Puji Pebrianti; Betty Holiwarni; Sunarti Sunarti; Asmadi M. Noer (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
The ability of students to solve problems is still low; therefore, a Higher Order Thinking Skills (HOTS)-based evaluation instrument through media is needed. This study aims to produce an evaluation instrument based on HOTS using Wondershare Quiz Creator (WQC) implemented to a valid ionic balance and pH buffer solution subject according to material and media experts. This research uses research and development (R&D) with the Plomp model. Besides, the research subjects are three teachers and 30 students in 11th grade from SMAN 8 Pekanbaru, SMAN 2 Pekanbaru, and MAN 1 Pekanbaru. Literature studies and field studies were carried out as the data collection techniques. The research data is obtained from the validation results of two material validators, two media validators, and user trials. The validation result to material validators has obtained the average based on the material aspect 96.00%, construction aspect 93.10%, and language aspect 99.00%. According to media validators, based on the content aspect 90.00%, learning design 84.00%, display (visual communication) 85.00%, and software utilization 95.71%. The analysis of the questions showed that ten questions were valid, had very high reliability, a medium difficulty level of five questions, and a difficult category of five questions and had good distinguishing power. User response scores are 88.00% by teachers and 95.23% by students with very good criteria.